Effect of feeding insecticide to cattle on growing and finishing rations - Harbers, L.H.; Pitts, C.W.; Harrision, K.F.; Tucker, L.L.; Smith, E.F. (Kansas State University. Agricultural Experiment Station, 2011)
A convenient method to control flies in cattle manure is adding an insecticide to the ration. The chemical passes through the digestive tract and effectively controls fly larvae in the manure. It may also influence animal performance. We added an insecticide at 50 p.p.m. to a high roughage growing ration and to an all-concentrate finishing ration and measured performance by growth, feed intake, and feed efficiency in steers and heifers.
Keywords: Beef; Insecticide; Growth; Feed intake; Feed efficiency